Gustatory sensing by ovipositor drives maternal avoidance of hesperidin to benefit the offspring in a major agricultural fly pest - Bao Dong; Yuanyuan Peng; Ruohan Kou; Hongfei Li; Fu Cao; Xinyu Lan; Jinjun Wang; Hongbo Jiang (Proceedings of the National Academy of Sciences, 2026)
Females of the oriental fruit fly ( Bactrocera dorsalis ) disproportionately oviposit in unripe fruits, despite their lower nutritional value compared to ripe fruits, but the sensory cues driving such counterintuitive site selection have not been determined. Here, using an oriental fruit fly–mango interaction system, we identified a specific flavonoid compound, hesperidin, as a major avoidance cue driving oviposition site selection in this species. Hesperidin accumulates as mango fruits ripen, and high concentrations suppress both larval growth and adult emergence. This indicates that higher levels of hesperidin exert a direct harmful effect on B. dorsalis larvae within ripe fruits. Interestingly, we found that B. dorsalis females perceive hesperidin via gustatory sensors on the ovipositor. The BdorGr28b gene is strongly expressed in the ovipositor, and we showed that the corresponding protein is the major hesperidin receptor. These results demonstrate that gustatory sensing via the ovipositor drives maternal avoidance of hesperidin to benefit the offspring in B. dorsalis . Our study provides insight into oviposition site selection in this species and the broader functional repertoire of insect gustation.